Exogenous poisoning in children due to the use of medicines in Brazil: Evaluation of the notification profile (Research, Society and Development, 2021)
Introduction: Exogenous drug intoxication affects the pediatric population through the risks of exposure and handling of drugs in homes, such as: placing attractive medications within easy reach of children and overdosing due to poor administration of those responsible. Objective: to evaluate the profile of notifications of exogenous intoxication in children involving the use of medications in Brazil. Methodology: This is a descriptive, exploratory and cross-sectional study using data from the Notifiable Diseases Information System of DATASUS from 2015 to 2019. The data were tabulated and organized by the Microsoft Excel 2016 software. The submission of the ethics committee was waived. Results: 43,989 cases of exogenous drug poisoning were reported in children in Brazil, in which the states of São Paulo, Minas Gerais and Pernambuco had higher percentage values, 20.0%, 12.3% and 11.7%, respectively. The age group between 1 and 4 years was the most affected (78.7%), mainly the male population (66.3%). Most of the cases occurred accidentally (69.4%) and acute-single exposure is the most frequent (83.7%). Conclusion: It is concluded that accidental exogenous drug intoxication continues as an aggravating condition in Brazil, especially in children under 5 years of age, male, accidental and acute-only.